Hydrocolloid-stabilized magnetite for efficient removal of radioactive phosphates - Vellora Thekkae Padil, Vinod; Rouha, Michael; Cerník, Miroslav (BioMed research international, 2014)
Liquid radioactive waste is a common by-product when using radioactive isotopes in research and medicine. Efficient remediation of such liquid waste is crucial for increasing safety during the necessary storage of the material. Herein, we present a novel Gum Karaya stabilized magnetite for the efficient removal of radioactive phosphorus (32)P from liquid radioactive waste. This environmentally friendly material is well suited to be used as a nanohydrogel for the removal of liquid waste, which can then be stored in a smaller space and without the risk of the spills inherent to the initial liquid material. The maximum adsorption capacity of the GK/M in this study was found to be 15.68 GBq/g. We present a thorough morphological characterization of the synthesised GK/M, as well as a discussion of the possible phosphorus adsorption mechanisms.
Keywords: Nanocomposites; Karaya Gum; Water Pollutants, Radioactive; Photoelectron Spectroscopy; Temperature; fotoelektronová spektroskopie; oxid železnato-železitý; radioaktivní odpad; teplota; guma karaya; Waste Disposal, Fluid; Kinetics; Adsorption; spektroskopie infračervená s Fourierovou transformací; Spectroscopy, Fourier Transform Infrared; difrakce rentgenového záření; X-Ray Diffraction; Ferrosoferric Oxide; Colloids; fosfáty; odpad tekutý - odstraňování; adsorpce; Radioactive Waste; kinetika; radioaktivní látky znečišťující vodu; Phosphates; koloidy; nanokompozity